1998
DOI: 10.1093/ee/27.6.1514
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of House Fly (Diptera: Muscidae) Larvae to Entomopathogenic Nematodes (Rhabditida: Heterorhabditidae, Steinernematidae)

Abstract: Entornopathogenic Nematodes (Rhabditida Heterorhabditidae, Midwest ldvestock k m Res-h Labratmy, =A-AM. Deparbnent of ~t o m~l o g y , University af N e b m k Lincoln, NE 68s83 f i v h n . Entomot. 27(6): 1514-1519 (1998) A B S l ' M m The potential for entornopathogenic nematodas to cantml flies in cattle feedlots was determined by screening 40 s h i n s repmenting 8 species of H~~ Poinar and 5 species of S~~ Travassos for virulence toward 3rd-instar house flies (maggots), Musm dmmtfm L None of the 22 s h i n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 10 publications
0
22
1
1
Order By: Relevance
“…Such a finding suggested either greater resistance of M. domestica larvae to the action of entomopathogenic nematodes or less virulence of the North Carolina strain when compared to the strain used in the present study. In contrast, Taylor et al (1998), who evaluated the pathogenicity of EPNs on larvae of M. domestica under experimental conditions similar to those used by Geden et al (1986), observed that Steinernema spp. were more virulent than Heterorhabditis spp., even mentioning that none of the species of Heterorhabditis used presented potential for control of the domestic fly.…”
Section: Bioassay With S Calcitrans Larvaementioning
confidence: 99%
“…Such a finding suggested either greater resistance of M. domestica larvae to the action of entomopathogenic nematodes or less virulence of the North Carolina strain when compared to the strain used in the present study. In contrast, Taylor et al (1998), who evaluated the pathogenicity of EPNs on larvae of M. domestica under experimental conditions similar to those used by Geden et al (1986), observed that Steinernema spp. were more virulent than Heterorhabditis spp., even mentioning that none of the species of Heterorhabditis used presented potential for control of the domestic fly.…”
Section: Bioassay With S Calcitrans Larvaementioning
confidence: 99%
“…were first inferred by analyses of sequence data of the ITS-1 region of the tandem repeat unit of rDNA (Adams et al, 1998). This study provided good resolution for closely related 'species' such as H. indica and H. hawaiiensis Gardner, Stock & Kaya (Rhabditida: Heterorhabditidae), H. bacteriophora and H. argentinensis Stock (Rhabditida: Heterorhabditidae).…”
Section: Steinernema and Heterorhabditismentioning
confidence: 94%
“…Of all considered and available methods, analysis of nucleotide sequence data has proven to be a useful tool not only for diagnostics at different taxonomic levels, but has also provided valuable data for phylogenetic inference of EPN (Adams et al, 1998;Liu, Berry, & Moldenke, 1997;Nadler, Bolotin, & Stock, 2006;Nguyen, Maruniak, & Adams, 2001;Stock, Campbell, & Nadler, 2001). At present two nuclear genes including partial sequence of the 28S rDNA gene ( 1Kb including the D2/D3 domain) and the complete Internal Transcribed Spacer (ITS) rDNA region (including ITS1, 5.8 S and ITS 2 genes) are the most widely used markers for diagnostics and assessment of phylogenetic relationships among taxa.…”
Section: Steinernema and Heterorhabditismentioning
confidence: 99%
See 1 more Smart Citation
“…Entomopathogenic nematodes such as Steinernema and Heterorhabditis spp. and their associated symbionts are virulent for fly larvae in certain substrates (41,44,55), but the harsh environments presented by poultry and swine manure are inimical to their survival (6,17,41,45).…”
Section: Cypoviruses Are Also Referred As Cytoplasmic Polyhedrosis VImentioning
confidence: 99%